Deep‐Level Defect Enhanced Photothermal Performance of Bismuth Sulfide–Gold Heterojunction Nanorods for Photothermal Therapy of Cancer Guided by Computed Tomography Imaging. (30th November 2017) - Cheng, Yan; Chang, Yun; Feng, Yanlin; Jian, Hui; Tang, Zhaohui; Zhang, Haiyuan
Abstract: Bismuth sulfide (Bi2 S3 ) nanomaterials are emerging as a promising theranostic platform for computed tomography imaging and photothermal therapy of cancer. Herein, the photothermal properties of Bi2 S3 nanorods (NRs) were unveiled to intensely correlate to their intrinsic deep‐level defects (DLDs) that potentially could work as electron–hole nonradiative recombination centers to promote phonon production, ultimately leading to photothermal performance. Bi2 S3 ‐Au heterojunction NRs were designed to hold more significant DLD properties, exhibiting more potent photothermal performance than Bi2 S3 NRs. Under 808 nm laser irradiation, Bi2 S3 ‐Au NRs could trigger higher cellular heat shock protein 70 expression and more apoptotic cells than Bi2 S3 NRs, and caused severe cell death and tumor growth inhibition, showing great potential for photothermal therapy of cancer guided by computed tomography imaging.